Prebiotic Properties and High-Density Culture of Bifidobacterium longum B2-01, a Strain Isolated from the Intestinal Tract of Infants - PENG Yunyan, ZHONG Shuying, LIU Dongmei, XU Xilin (Shipin Kexue)
In this study, a Lactobacillus strain was isolated from the feces of healthy 3-month-old infants in Guangzhou, identified and named as Bifidobacterium longum B2-01 by molecular biology, and its probiotic properties, such as in vitro antioxidant activity and hepatoprotective activity, and high-density culture were investigated. The results showed that B2-01 had a strong ability to scavenge 1,1-diphenyl-2-picrylhydrazyl (DPPH), hydroxyl, superoxide anion, and 2,2’-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) cation radicals and to resist lipid peroxidation. At the highest concentration of 10% (V/V) in the fermentation supernatant of DMEM medium, strain B2-01 increased the survival rates of L02 cells against hydrogen peroxide damage and alcohol damage to 89.10% and 91.38%, respectively, while significantly reducing the transaminase activity in hepatocytes. The optimal conditions for high-density culture were determined as follows: yeast extract concentration 3.45%, glucose concentration 2.48%, lactose concentration 2.79%, bacteriological peptone concentration 3%, and oligogalactose concentration 2.5%. Under these conditions, the maximum viable bacterial count of 4.20 × 109 CFU/mL was observed in the fermentation broth, which was 6.45 times as high as that before optimization (7.71 × 108 CFU/mL).